Suitable Specimen Types for Newborn Biochemical Screening-A Summary - Kate Hall (MDPI AG, 2017)
Newborn biochemical screening has been in place in many countries for over fifty years initially testing dried skin puncture whole blood spotted on collection paper (DBS) or urine for phenylalanine or phenylketones to identify phenylketonuria. Countries wishing to commence newborn screening need to consider which type of specimen will provide a satisfactory specimen and matrix for testing for disorders relevant to their population, is acceptable to parents and can be readily transported to the analytical or laboratory facility without significant degradation. Whilst DBSs have largely become the specimen of choice they may not be applicable to all cultures and infrastructures. The majority of disorders appropriate to be identified in the newborn period can be detected in DBSs taken shortly after birth. Some are also detectable in cord blood or urine, some are not. Most disorders have an ideal and often different time window of age for identification in relation to treatment for optimum outcome. When embarking on newborn screening for the first time or in expanding what is already in place, it is important that the disorders considered are evaluated against the Wilson and Jungner criteria for population screening. A brief overview of specimen types including urine, cord blood and DBSs with some of their advantages and limitations is provided in this review to assist in decision-making.